La parasitosis y a relación con los factores socio ambientales en los menores de 5 años de la comunidad nuevo Babahoyo de la parroquia clemente Baquerizo, cantón Babahoyo provincia de Los Ríos durante el primer semestre del 2013 - Gallegos Barroso, Marjorie Elina (2013)
Our research we have conducted in order to know that the relationship has parasitosis with socio-environmental factors in children under five years of the New Babahoyo urban parish community Clemente Baquerizo Region Babahoyo province of Los Ríos in the first half of 2013. Its purpose is to reduce mortality and morbidity in children under five , as well as advance their growth and development. The type of research used is of experimental , descriptive , transversal, as data collection instrument Quasi survey , with its own questionnaire , the same as I consist of 10 items with response options was used ...............